Supremo Tribunal Federal e Estado de direito: a gestão da pauta de julgamento em perspectiva - Victor Bicalho Cruz Amaral Quirino (2021)
This research aims to understand the procedure of definition of the Brazilian Supreme Court’s judgments agenda in light of a conception of the Rule of Law. It is also sought to understand how the agenda power can be operationalized by the presidency of the Court, and to what extent its exercise, which is done individually and not collectively, can affect the relationship between the institutions and the very function to be performed by the Brazilian Supreme Court. From the analysis of a real case on the judicial review of the possibility of early execution of the condemnatory sentence, the research intends to critically analyze the power to define the judgment agenda, mobilizing, for that, the concept of Rule of Law, under its different – but complementary – facets and characteristics.